The Significance of Chloroplast NAD(P)H Dehydrogenase Complex and Its Dependent Cyclic Electron Transport in Photosynthesis - Ma, Mingzhu; Liu, Yifei; Bai, Chunming; Yong, Jean Wan Hong (Frontiers in Plant Science, 2021)
Chloroplast NAD(P)H dehydrogenase (NDH) complex, a multiple-subunit complex in the thylakoid membranes mediating cyclic electron transport, is one of the most important alternative electron transport pathways. It was identified to be essential for plant growth and development during stress periods in recent years. The NDH-mediated cyclic electron transport can restore the over-reduction in stroma, maintaining the balance of the redox system in the electron transfer chain and providing the extra ATP needed for the other biochemical reactions. In this review, we discuss the research history and the subunit composition of NDH. Specifically, the formation and significance of NDH-mediated cyclic electron transport are discussed from the perspective of plant evolution and physiological functionality of NDH facilitating plants’ adaptation to environmental stress. A better understanding of the NDH-mediated cyclic electron transport during photosynthesis may offer new approaches to improving crop yield.